Development of Science Learning Packages for Developing Life Skill Course in Vocational Certification - Thepparat, Thidarat (Journal of Advanced Development in Engineering and Science, 2023)
The purposes of this research were to design and evaluate the efficiency of Science Learning Packages (SLP) for developing life skill. The designed SLP was subsequently evaluated its efficiency by Try-out based on Process-E1 and Product -E2 using E1/E2 at 75/75 criteria. Then it was applied for Trail Run to compare the integrated science process skill and student achievement from pre-test and post-test of this designed SLP. The sample was selected for 30 students using purposive sampling from the 1st year students in the 2nd semester of academic year 2013 in Agriculture and Technology, vocational certification, Nakhon Si Thammarat College. The instruments were SLP tests the integrated science process skills tests and the achievement tests. Statistical analyzing were mean, standard deviation and t-test. The results showed that this designed SLP was consisted of explanation framework, learning topic, objective, science process skill, content sheets, laboratory and application manual. From try-out, the effective result (E1/E2) was 75.93/75.44. After the teaching efficiency was tested by using the test of integrated science process skills, the results of the pre-test of 14.90 and the post-test of 30.37 showed the students’ achievement. The test of learning achievement showed the pre-test of 15.77 and the post-test of 33.10 that the post-test was higher than the pre-test at the significant level of 0.05.